Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/0009922811425234
|View full text |Cite
|
Sign up to set email alerts
|

Non-IgE-Mediated Cow Milk Allergy Is Linked to Early Childhood Clusters of Commonly Seen Illnesses

Abstract: A global evaluation of multiple systems can be an important diagnostic tool in determining CMPA in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Cow’s milk is not recommended until after 12 months of age, because its composition is significantly different to breast milk and infant formula, and its use can lead to iron deficiency [36, 37]. Another consideration is cow’s milk protein allergy, which is associated with TTP [38]. We did not find infant formula to be a risk factor, even though it usually contains cow’s milk.…”
Section: Discussionmentioning
confidence: 94%
“…Cow’s milk is not recommended until after 12 months of age, because its composition is significantly different to breast milk and infant formula, and its use can lead to iron deficiency [36, 37]. Another consideration is cow’s milk protein allergy, which is associated with TTP [38]. We did not find infant formula to be a risk factor, even though it usually contains cow’s milk.…”
Section: Discussionmentioning
confidence: 94%
“…Gibbons et al aimed to evaluate a multisystem questionnaire that would help diagnose non-Ig-E-mediated early CMPA and be easy to apply and score in a busy clinical setting. 7 Symptoms for the questionnaire were selected based on chart reviews of patients diagnosed with CMPA and a literature review of its clinical manifestations in infants. Each symptom scores 1 for a positive response, and 0 for a negative response, and an overall score was calculated (see Figure 3).…”
Section: Cmpa Questionnairementioning
confidence: 99%
“…Methodological quality was poor in the risk of bias domains, where all studies scored high risk in at least two domains. Three studies were at high risk in the patient selection domain; two used a case-control study design, 7,8 and one study did not use a consecutive or random sampling method, but instead included only infants that scored a CoMiSS TM of > 12. 23 Three studies demonstrated high risk of index test interpretation bias, due to the lack of pre-specified threshold criterion for a positive screen and a lack of blinding to the results of the reference standard.…”
Section: Development and Piloting Studiesmentioning
confidence: 99%
See 2 more Smart Citations